Variability of Microcystin-LR Standards Available from Seven Commercial Vendors - Donna Hill; Johnsie Lang; James McCord; Mark Strynar; Charlita Rosal; Judith Schmid; Thanh-Thao Le; Neil Chernoff (Toxins, 2022)
Microcystins (MCs) are a large group of heptapeptide cyanobacterial toxins commonly produced in harmful algal blooms (HABs) and associated with adverse health effects in wildlife, livestock, pets, and humans. MC chemical standards are extracted from cyanobacteria biomass rather than produced synthetically and are used in water assessment methods and toxicological studies. MC standards are generally supplied in less than 1 mg quantities, and verification of the mass can only be accomplished by analytical chemistry methods using a certified reference of the specific MC for comparison. Analytical quantification of MCs in environmental samples and toxicology studies using accurate doses of test chemicals administered to experimental animals rely on the availability and accuracy of chemical standards. To check the accuracy and purity of available standards, seven individual microcystin-LR (MCLR) standards were purchased from separate commercial vendors and analyzed to determine the actual mass supplied and identify the presence of potential contaminants. To determine the effect of varying toxin mass in toxicological studies, each MCLR standard was administered to CD-1 mice in doses based on mass purchased, by a single 40 µg/kg intraperitoneal injection. The measured mass purchased varied from the vendor label mass by more than 35% for two of the seven MCLR standards. Contaminants, including trifluoroacetic acid (TFA), were identified in four of the seven samples. Comparative in vivo hepatotoxicity between vendor samples closely reflected the actual amount of MCLR present in each standard and demonstrated the toxicological impact of varying cyanotoxin mass.